ANALISIS KNOWLEDGE MANAGEMENT DAN TALENT MANAGEMENT TERHADAP EMPLOYEE ENGAGEMENT - KATARINA PINGKAN; COKORDA GEDE PUTRA YUDISTIRA; UPAYANA WIGUNA EKA SAPUTRA (Universitas Mahasaraswati K. Mataram, 2023)
Employees who feel engaged to the company will work optimally and are committed. Therefore, the company must optimize the available human resources. The purpose of this research is to analyze and explain the partial and simultaneous effect of knowledge management and talent management on employee engagement at the Holiday Inn Resort Bali Nusa Dua and to find out the efforts to increase employee engagement. The population of this study is 115 employees (contract and permanent). The sample used is 90 people using the Isaac and Michael formula. This study used a quantitative approach with multiple linear regression analysis methods. The results of this study indicate that knowledge management and talent management, has a significant positive effect on employee engagement at the Holiday Inn Resort Bali Nusa Dua. Knowledge management and talent management simultaneously have a significant positive effect on employee engagement at the Holiday Inn Resort Bali Nusa Dua. Knowledge management has a dominant influence on employee engagement. Knowledge management contributes 32.6% to employee engagement while talent management contributes 19.8% to employee engagement. Employee engagement can be explained by 38.8% knowledge management and talent management variables, the rest is explained by other factors or variables outside of this research